Bio-IGRT - Yaromina, A.; Zips, D. (Nuklearmedizin - NuclearMedicine, 2010)
Image-guided radiotherapy (IGRT) represents a novel method to precisely deliver radiation to tumours while sparing surrounding normal tissues. Integration of biological imaging using PET or MRI appears to be a promising concept to improve radiotherapy (Bio-IGRT). For this it is essential that biological imaging provides radiobiologically relevant information. Preclinical and clinical investigations into validation of PET tracers and MR methods in the context of curative radiotherapy and of concepts for biology-based escalation of radiation dose as well as other therapeutic interventions are an important task for further cancer research.
Keywords: Image-guided radiotherapy; biological factors of radiation resistance of tumours; radiation biology; hypoxia